Approach to the cultural consumption of undergraduate economics students in Puebla, Mexico - Romero Amado, Jorge (Última Década, 2020)
The purpose of the following article is to know, to discern and to describe thehabits, influences and means of cultural consumption of freshmen from theFaculty of Economics at Benemérita Universidad Autónoma de Puebla. Asurvey consisting of single and multiple-choice questions was conducted,showing that the consumption of music and series is encouraged at home, beingthe former their favorite cultural product. These products are mainly consumedon the internet and on their mobile phones and they are largely from the UnitedStates. The most direct influences for its consumption are from parents andfriends.